Risk factors for on-farm mortality in beef suckler cows under extensive keeping management. (August 2017) - Mõtus, Kerli; Emanuelson, Ulf
Abstract: The on-farm mortality of cows in cow-calf herds has a significant influence on the economic efficiency of the farm. It is also an indicator of suboptimal animal health and welfare. The present study analysed the registry data of beef cows in Estonia from the years 2013 to 2015. The datasets incorporated 8084 parturitions of primiparous cows and 21, 283 parturitions of 9234 multiparous cows. A Weibull proportional hazard random effect model was used for risk factor analysis, in which the on-farm mortality, including death and euthanasia, was the event of interest. The first 30 days post-calving were associated with the highest mortality hazard for primiparous and multiparous cows (including 28.9% and 21.1% of deaths, respectively). In multiparous cows, the lowest mortality hazard was confirmed for animals with parity of three to five, increasing significantly after that. Primiparous cows that did not have a stillborn calf had a significantly higher mortality hazard when calving over 44 months of age compared to cows calving younger than 36 months. Stillbirth and abortion were significant risk factors for mortality. Cows with dystocia experienced a higher mortality hazard, especially during the first week post-calving. In multiparous cows, a higher herd mean age at first calving was associated with a higher mortality hazard. This study highlights the fact that the early post-partum period and factors associated with calving, such as age at first calving, dystocia, stillbirth and abortion, are critical for beef cow survival. Highlights: Highest mortality hazard occurred at first 30 days post-calving. Parity of three to five had lowest mortality hazard in multiparous cows. Dystocia, abortion and stillbirth were associated with increased mortality hazard in cows. Higher age at first calving was associated with increased mortality hazard. Most of the herd factors were not associated with cow on-farm mortality hazard.